PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD MUHAMMADIYAH 4 PEKANBARU - Mayang Suci Padrina Suci Padrina; Lazim. N Lazim. N '; Damanhuri Daud Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : background of this study is the low outocomes of natural science (IPA) of the fourth grade students of IV SD Muhammadiyah 4 Pekanbaru, with the average score of the class is 58,54. Based on the standard minimum criteria (KKM) 70 which has been determined by the school, there were 20 stedents are below the standard minimum criteria or 60,61% and 13 students are above the minimum standard criteria or 39,39% from overal number of 33 students. This research is an actions research which aims to enhance learning outocomes natural science (IPA) grade students of IV SD Muhammadiyah 4 Pekanbaru with the implementation of model inkuiry. Formulation of the problem: does model inkuiry can increase natural science (IPA) autocomes of students at class IV SD Mmuhammadiyah 4 Pekanbaru?. This research was carried out on 30 April 2015 until 21 May 2015 with II cycles. The subject of this research is students at class IV SD Muhammadiyah 4 Pekanbaru with total number 33 stedents who were bacame the participants of this research. Data collection instruments in this research are teacher and studets activity sheets as well as a written test sheet. The result of this research can bee seen from the result of the study before the implementation of inkuiry model are given which the average score 58,54 after the action is given or after implementation of inkuiry model are increased in cycle I, with an average score 71,03 which are increased as much as 21,33% and cycle II the average score 82,06 which are increased as much as 40,17%. It can be concluded that the inkuiry model can increase natural science (IPA) autocomes of students at class IV SD Mmuhammadiyah 4 Pekanbaru .Keywords : Inkuiry model, IPA Study Results.